Nias Islands expansion urgency through top-down strategy in Indo-Pacific and the Indian Ocean - Waruwu, Yusadar; Juwono, Vishnu (Indonesian Journal of Multidisciplinary Science, 2023)
The expansion of Nias Islands Province is the desire of the political community. However, until now, the expansion effort has not received central government approval. Threats to the region can come from a variety of sources and forms, including internal conflicts, transnational conflicts, and military threats. This research aims to analyze the urgency of the expansion of Nias Islands through a top-down strategy, considering national threats and strategic factors. The research method used was an analytical descriptive approach with a qualitative type of research. Data were obtained through interviews and observations, as well as primary and secondary data relevant to the expansion of Nias Islands Province. The results show the urgency of the expansion of Nias Islands involving a top-down strategy by considering threat factors and national strategic policies. The relevance of the formation of Nias Islands Province can be seen from geographical, geopolitical, and demographic factors. The readiness of this region to become a New Autonomous Region (DOB) is reflected in agreements between regional heads, infrastructure availability, and financial support during the transition. The central government needs to understand that the expansion of Nias Islands is not only a local need but also a strategic step in maintaining national security and stability.